14) x=0, y=3, z=-2
Solution Set (0,3,-2)
16) x=1, y=1 and z=1
Solution set = (1,1,1)
20) x = -263/31, y=164/31 ,z=122/31
Solution set (-263/31, 164/31 ,122/31)
Step-by-step explanation:
14)
![x-y+2z=-7\\y+z=1\\x=2y+3z](https://tex.z-dn.net/?f=x-y%2B2z%3D-7%5C%5Cy%2Bz%3D1%5C%5Cx%3D2y%2B3z)
Rearranging and solving:
![x-y+2z=-7\,\,\,eq(1)\\y+z=1\,\,\,eq(2)\\x-2y-3z=0\,\,\,eq(3)](https://tex.z-dn.net/?f=x-y%2B2z%3D-7%5C%2C%5C%2C%5C%2Ceq%281%29%5C%5Cy%2Bz%3D1%5C%2C%5C%2C%5C%2Ceq%282%29%5C%5Cx-2y-3z%3D0%5C%2C%5C%2C%5C%2Ceq%283%29)
Eliminate y:
Adding eq(1) and eq(2)
![x-y+2z=-7\,\,\,eq(1)\\ 0x+y+z=1\,\,\,eq(2)\\-------\\x+3z=-6\,\,\,eq(4)](https://tex.z-dn.net/?f=x-y%2B2z%3D-7%5C%2C%5C%2C%5C%2Ceq%281%29%5C%5C%200x%2By%2Bz%3D1%5C%2C%5C%2C%5C%2Ceq%282%29%5C%5C-------%5C%5Cx%2B3z%3D-6%5C%2C%5C%2C%5C%2Ceq%284%29)
Multiply eq(2) with 2 and add with eq(3)
![0x+2y+2z=2\,\,\,eq(2)\\\\x-2y-3z=0\,\,\,eq(3)\\--------\\x-z=2\,\,\,eq(5)](https://tex.z-dn.net/?f=0x%2B2y%2B2z%3D2%5C%2C%5C%2C%5C%2Ceq%282%29%5C%5C%5C%5Cx-2y-3z%3D0%5C%2C%5C%2C%5C%2Ceq%283%29%5C%5C--------%5C%5Cx-z%3D2%5C%2C%5C%2C%5C%2Ceq%285%29)
Eliminate x:
Subtract eq(4) and eq(5)
![x+3z=-6\,\,\,eq(4)\\x-z=2\,\,\,eq(5)\\-\,\,\,+\,\,\,\,\,\,-\\---------\\4z=-8\\z= -2](https://tex.z-dn.net/?f=x%2B3z%3D-6%5C%2C%5C%2C%5C%2Ceq%284%29%5C%5Cx-z%3D2%5C%2C%5C%2C%5C%2Ceq%285%29%5C%5C-%5C%2C%5C%2C%5C%2C%2B%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C-%5C%5C---------%5C%5C4z%3D-8%5C%5Cz%3D%20-2)
So, value of z = -2
Now putting value of z in eq(2)
![y+z=1\\y+(-2)=1\\y-2=1\\y=1+2\\y=3](https://tex.z-dn.net/?f=y%2Bz%3D1%5C%5Cy%2B%28-2%29%3D1%5C%5Cy-2%3D1%5C%5Cy%3D1%2B2%5C%5Cy%3D3)
So, value of y = 3
Now, putting value of z and y in eq(1)
![x-y+2z=-7\\x-(3)+2(-2)=-7\\x-3-4=-7\\x-7=-7\\x=-7+7\\x=0](https://tex.z-dn.net/?f=x-y%2B2z%3D-7%5C%5Cx-%283%29%2B2%28-2%29%3D-7%5C%5Cx-3-4%3D-7%5C%5Cx-7%3D-7%5C%5Cx%3D-7%2B7%5C%5Cx%3D0)
So, value of x = 0
So, x=0, y=3, z=-2
S.S(0,3,-2)
16)
![3x-y+z=3\\\x+y+2z=4\\x+2y+z=4](https://tex.z-dn.net/?f=3x-y%2Bz%3D3%5C%5C%5Cx%2By%2B2z%3D4%5C%5Cx%2B2y%2Bz%3D4)
Let:
![3x-y+z=3\,\,\,eq(1)\\x+y+2z=4\,\,\,eq(2)\\x+2y+z=4\,\,\,eq(3)](https://tex.z-dn.net/?f=3x-y%2Bz%3D3%5C%2C%5C%2C%5C%2Ceq%281%29%5C%5Cx%2By%2B2z%3D4%5C%2C%5C%2C%5C%2Ceq%282%29%5C%5Cx%2B2y%2Bz%3D4%5C%2C%5C%2C%5C%2Ceq%283%29)
Eliminating y:
Adding eq(1) and (2)
![3x-y+z=3\,\,\,eq(1)\\x+y+2z=4\,\,\,eq(2)\\---------\\4x+3z=7\,\,\,eq(4)](https://tex.z-dn.net/?f=3x-y%2Bz%3D3%5C%2C%5C%2C%5C%2Ceq%281%29%5C%5Cx%2By%2B2z%3D4%5C%2C%5C%2C%5C%2Ceq%282%29%5C%5C---------%5C%5C4x%2B3z%3D7%5C%2C%5C%2C%5C%2Ceq%284%29)
Multiply eq(1) by 2 and add with eq(3)
![6x-2y+2z=6\,\,\,eq(1)\\x+2y+z=4\,\,\,eq(3)\\---------\\7x+3z=10\,\,\,eq(5)](https://tex.z-dn.net/?f=6x-2y%2B2z%3D6%5C%2C%5C%2C%5C%2Ceq%281%29%5C%5Cx%2B2y%2Bz%3D4%5C%2C%5C%2C%5C%2Ceq%283%29%5C%5C---------%5C%5C7x%2B3z%3D10%5C%2C%5C%2C%5C%2Ceq%285%29)
Now eliminating z in eq(4) and eq(5) to find value of x
Subtracting eq(4) and eq(5)
![4x+3z=7\,\,\,eq(4)\\7x+3z=10\,\,\,eq(5)\\-\,\,\,-\,\,\,\,\,\,\,\,\,\,-\\-----------\\-3x=-3\\x=-3/-3\\x=1](https://tex.z-dn.net/?f=4x%2B3z%3D7%5C%2C%5C%2C%5C%2Ceq%284%29%5C%5C7x%2B3z%3D10%5C%2C%5C%2C%5C%2Ceq%285%29%5C%5C-%5C%2C%5C%2C%5C%2C-%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C-%5C%5C-----------%5C%5C-3x%3D-3%5C%5Cx%3D-3%2F-3%5C%5Cx%3D1)
So, value of x = 1
Putting value of x in eq(4) to find value of x:
![4x+3z=7\\4(1)+3z=7\\4+3z=7\\3z=7-4\\z=3/3\\z=1](https://tex.z-dn.net/?f=4x%2B3z%3D7%5C%5C4%281%29%2B3z%3D7%5C%5C4%2B3z%3D7%5C%5C3z%3D7-4%5C%5Cz%3D3%2F3%5C%5Cz%3D1)
So, value of z = 1
Putting value of x and z in eq(2) to find value of y:
![x+y+2z=4\\1+y+2(1)=4\\1+y+2=4\\y+3=4\\y=4-3\\y=1](https://tex.z-dn.net/?f=x%2By%2B2z%3D4%5C%5C1%2By%2B2%281%29%3D4%5C%5C1%2By%2B2%3D4%5C%5Cy%2B3%3D4%5C%5Cy%3D4-3%5C%5Cy%3D1)
So, x=1, y=1 and z=1
Solution set = (1,1,1)
20)
![x+4y-5z=-7\\3x+2y+2z=-7\\2x+y+5z=8](https://tex.z-dn.net/?f=x%2B4y-5z%3D-7%5C%5C3x%2B2y%2B2z%3D-7%5C%5C2x%2By%2B5z%3D8)
Let:
![x+4y-5z=-7\,\,\,eq(1)\\3x+2y+2z=-7\,\,\,eq(2)\\2x+y+5z=8\,\,\,eq(3)](https://tex.z-dn.net/?f=x%2B4y-5z%3D-7%5C%2C%5C%2C%5C%2Ceq%281%29%5C%5C3x%2B2y%2B2z%3D-7%5C%2C%5C%2C%5C%2Ceq%282%29%5C%5C2x%2By%2B5z%3D8%5C%2C%5C%2C%5C%2Ceq%283%29)
Solving:
Eliminating z :
Adding eq(1) and eq(3)
![x+4y-5z=-7\,\,\,eq(1)\\2x+y+5z=8\,\,\,eq(3)\\---------\\3x+5y=1\,\,\,eq(4)](https://tex.z-dn.net/?f=x%2B4y-5z%3D-7%5C%2C%5C%2C%5C%2Ceq%281%29%5C%5C2x%2By%2B5z%3D8%5C%2C%5C%2C%5C%2Ceq%283%29%5C%5C---------%5C%5C3x%2B5y%3D1%5C%2C%5C%2C%5C%2Ceq%284%29)
Multiply eq(1) with 2 and eq(2) with 5 and add:
![2x+8y-10z=-14\,\,\,eq(1)\\15x+10y+10z=-35\,\,\,eq(2)\\----------\\17x+18y=-49\,\,\,eq(5)](https://tex.z-dn.net/?f=2x%2B8y-10z%3D-14%5C%2C%5C%2C%5C%2Ceq%281%29%5C%5C15x%2B10y%2B10z%3D-35%5C%2C%5C%2C%5C%2Ceq%282%29%5C%5C----------%5C%5C17x%2B18y%3D-49%5C%2C%5C%2C%5C%2Ceq%285%29)
Eliminate y:
Multiply eq(4) with 18 and eq(5) with 5 and subtract:
![54x+90y=18\\85x+90y=-245\\-\,\,\,-\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,+\\-------\\-31x=158\\x=-\frac{263}{31}](https://tex.z-dn.net/?f=54x%2B90y%3D18%5C%5C85x%2B90y%3D-245%5C%5C-%5C%2C%5C%2C%5C%2C-%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%2B%5C%5C-------%5C%5C-31x%3D158%5C%5Cx%3D-%5Cfrac%7B263%7D%7B31%7D)
So, value of x = -263/31
Putting value of x in eq(4)
![3x+5y=1\\3(-\frac{263}{31})+5y=1\\-\frac{789}{31}+5y=1 \\5y=1+\frac{789}{31}\\5y=\frac{820}{31}\\y=\frac{820}{31*5}\\y=\frac{164}{31}](https://tex.z-dn.net/?f=3x%2B5y%3D1%5C%5C3%28-%5Cfrac%7B263%7D%7B31%7D%29%2B5y%3D1%5C%5C-%5Cfrac%7B789%7D%7B31%7D%2B5y%3D1%20%5C%5C5y%3D1%2B%5Cfrac%7B789%7D%7B31%7D%5C%5C5y%3D%5Cfrac%7B820%7D%7B31%7D%5C%5Cy%3D%5Cfrac%7B820%7D%7B31%2A5%7D%5C%5Cy%3D%5Cfrac%7B164%7D%7B31%7D)
Now putting x = -263/31 and y=164/31 in eq(1) and finding z:
We get z=122/31
So, x = -263/31, y=164/31 ,z=122/31
Solution set (-263/31, 164/31 ,122/31)
Keywords: Solving system of Equations
Learn more about Solving system of Equations at:
#learnwithBrainly